Crusaders and Franks - Ḳedar, B. Z., author. Link
1 online resource.
Keywords: While research on the crusades tends increasingly to bifurcate into study of the crusade idea and the crusading expeditions, and study of the Frankish states the crusaders established in the Levant, Benjamin Kedar confirms-through the articles reproduced in this latest selection of his articles-his adherence to the school that endeavours to deal with both branches of research. Of the ten studies that deal with the crusading expeditions, one examines the maps that might have been available to the First Crusaders and their Muslim opponents, another discusses in detail the Jerusalem massacre of July 1099 and its place in Western historiography down to our days, a third sheds light on the largely neglected doings of the Fourth Crusaders who decided to sail to Acre rather than to Constantinople, while a fourth exposes unknown features of the well-known sculpture of the returning crusader-most probably Count Hugh I of Vaudmont- who is embracing his wife. Of the ten studies that deal with the Frankish Levant, one proposes a hypothesis on the composition stages of William of Tyre's chronicle, another provides new evidence on the Latin hermits who chose to live in the Frankish states, a third examines the catalogue of the library of the cathedral of Nazareth, while a fourth calls attention to convergences of Eastern Christians, Muslims and Franks in sacred spaces and offers a typology of such events, and a fifth proposes a methodology for the identification of trans-cultural borrowing in the Frankish Levant.